Amblyomma americanum tick saliva insulin‐like growth factor binding protein‐related protein 1 binds insulin but not insulin‐like growth factors. Issue 5 (25th June 2015) - Radulović, Ž. M.; Porter, L. M.; Kim, T. K.; Bakshi, M.; Mulenga, A.
Abstract Silencing Amblyomma americanum insulin‐like growth factor binding protein‐related protein 1 (AamIGFBP‐rP1) mRNA prevented ticks from feeding to repletion. In this study, we used recombinant (r)AamIGFBP‐rP1 in a series of assays to obtain further insight into the role(s) of this protein in tick feeding regulation. Our results suggest that AamIGFBP‐1 is an antigenic protein that is apparently exclusively expressed in salivary glands. We found that both males and females secrete AamIGFBP‐rP1 into the host during feeding and confirmed that female ticks secrete this protein from within 24–48 h after attachment. Our data suggest that native AamIGFBP‐rP1 is a functional insulin binding protein in that both yeast‐ and insect cell‐expressed rAamIGFBP‐rP1 bound insulin, but not insulin‐like growth factors. When subjected to anti‐blood clotting and platelet aggregation assays, rAamIGFBP‐rP1 did not have any effect. Unlike human IGFBP‐rP1, which is controlled by trypsinization, rAamIGFBP‐rP1 is resistant to digestion, suggesting that the tick protein may not be under mammalian host control at the tick feeding site. The majority of tick‐borne pathogens are transmitted 48 h after the tick has attached. Thus, the demonstrated antigenicity and secretion into the host within 24–48 h of the tick starting to feed makes AamIGFBP‐rP1 an attractive target for antitick vaccine development.